The shadow of death: an empirical analysis of the pre-exit performance of young German firms - Matthias Almus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
This paper makes an empirical contribution to confirm the stylized fact that the performance of firms deteoriates in the years before exit. For this reason we evaluate whether market exits differ significantly in their employment development in the years before market drop-out compared to surviving firms that have been selected using a non-parametric matching approach. The matching approach allows to find a surviving firm for every market exit that does not differ in important characteristics measured at start-up. The comparison of the employment growth rates among the thus formed groups reveals that the matched surviving firms experience higher growth rates compared to their exiting counterparts up to three years before market exit. Moreover, we find support for the phenomenon called of death" sneaking around the corner. A considerable number of firms exiting from 1995 until 1998 has experienced continuing employment losses or at least an employment stagnation over several years before market exit.
Keywords: C14; L21; 330; New Firms; Employment Growth; Evaluation; Non-Parametric Matching; Marktaustritt; Krisenmanagement; Unternehmensgründung; Unternehmensentwicklung; Beschäftigungseffekt; Erfolgsfaktor; Schätzung; Deutschland